Treatment of refractory dissecting cellulitis of the scalp with guselkumab: Case report - Sonal Muzumdar; Sonal Parikh; Bruce Strober (Wolters Kluwer Medknow Publications, 2020)
Dissecting cellulitis (DC) of the scalp is a chronic, clinically refractory inflammatory skin disorder. Herein is a presentation of a male with refractory DC with concurrent hidradenitis suppurativa, who had failed treatment with multiple topical and systemic therapies. After receiving guselkumab, 100 mg subcutaneously every 8 weeks, the patient exhibited marked improvement, with normalization of symptoms and signs.